Analysis Of Solid Waste Management (Swm) Situation In 10 Urban Cities Of India And Raising Public Awareness Among Households (Journal of Namibian Studies : History Politics Culture, 2023)
Global Solid Waste Management has become a severe challenge as a result of modern lifestyles that place a high priority on consumption and disposal. Pressure on our planet's land space exacerbates the issue. Wet and dry materials make up the diverse types of urban solid waste. Waste results in a significant waste of resources, including materials and energy. In fact, the amount of garbage generated might be seen as a measure of society's materialism. The aim of the study is to assess public awareness of solid waste management (SWM) of 10 urban cities of India. For the purpose of gathering the data for this descriptive study, a variety of methods were used. A descriptive and experimental design involves the process of collecting, assessing, and "combining" either qualitative and quantitative information and approaches in a continuous study to understand a research methodology. Delhi and Kolkata generated less waste per household than all the other cities combined. Overall, 55% of homes produce around 1 kilogramme of garbage, and 34% produce about 1/2 kg. Only 11% of families, or a small percentage, did not know how much garbage their houses produce. Segregation of waste is the most important part of Municipal SWM and also this research; this was discussed in detail with the households.